Tourism Manager's Strategy in Creating Environmental Awareness for Visitors: Environmental Study of Kereng Bangkirai Pier - Adis Extrada; Serniyati; Nazwa Aqila Nuraisyah; Saputra Adiwijaya; Muhammad Zusanri Batubara; Elia Damayanti (PT Polstac Repositori Riset, 2026)
Background: This study aims to analyze tourism managers' strategies in creating environmental awareness for visitors through information board media at Kereng Bangkirai Pier. Environmental awareness is an important aspect in sustainable tourism management, but there are still problems related to the lack of optimal information media in increasing visitor awareness. Contribution: Using the theory of Stimulus-Organism-Response (SOR), this study examines how the stimulus components (visual quality, ease of information, board design), organism components (emotions, expectations, perception of professionalism), and response components (area exploration, duration of visit, recommendations) affect the environmental awareness of visitors. Method. The research method uses a qualitative approach with in-depth interview techniques with tour managers and visitors. Results: The results of the study show that strategic, informative, and visually appealing information board media can significantly increase visitors' environmental awareness. This research makes a practical contribution for tourism managers in optimizing environmental communication strategies through effective information media.